Rekonstruksi Epistemologis Metodologi Penelitian Hukum: Integrasi Pendekatan Normatif dan Empiris - Tasrizal (LP3M Sekolah Tinggi Ilmu Hukum Al-Banna, 2025)
Conventional legal research in Indonesia has generally been dominated by a normative-doctrinal approach that emphasizes systematic analysis of legal texts (law in books). In contrast, empirical or sociological approaches (law in action) focus on social realities and legal behavior within society. This article undertakes an epistemological comparison of these two approaches in the context of contemporary legal issues, examining their respective strengths and limitations, and proposing a reflective-integrative methodological model. The study demonstrates that the normative approach excels in system construction and prescriptive analysis, whereas the empirical approach is stronger in generating evidence and contextual understanding. Accordingly, the integration of normative, empirical, and socio-legal approaches through a reflective-integrative methodological framework is necessary to produce legal research that is more comprehensive, adaptive, and evidence-based.